MURCHA BACTERIANA DO GERÂNIO CAUSADA POR Ralstonia solanacearum BIOVAR 2/RAÇA 3 NO BRASIL - Almeida, Irene M. G.; Destéfano, Suzete A. L.; Rodrigues Neto, Júlio; Malavolta Jr, Valdemar A. (REVISTA DE AGRICULTURA, 2015)
MURCHA BACTERIANA DO GERÂNIO CAUSADA POR Ralstonia solanacearum BIOVAR 2/RAÇA 3 NO BRASIL